Peer mentoring programs for nursing students: A mixed methods systematic review. (December 2022) - Lim, Siriwan; Xin Min, Lim; Chan, Cheryl Jia Wen; Dong, YanHong; Mikkonen, Kristina; Zhou, Wentao
Abstract: Background: Peer mentoring in nursing is imperative to both mentors' and mentees' personal and professional development. Yet, there is a dearth of reviews appraising the relevant qualitative and quantitative studies reported in the literature. Objectives: To synthesize the best evidence exploring the impacts of peer mentoring programs on nursing students. Design: A mixed-method systematic review. Data sources: Published and unpublished literature written in English between January 2011 and May 2022 were identified from nine databases, including PubMed, CINAHL, Cochrane Library, Embase, and PsycINFO. Review methods: A systematic search strategy was applied in June 2021. Two reviewers independently screened and selected the eligible studies focusing on nursing students in higher education institutions who participated in peer mentoring programs. We included studies of quantitative, qualitative, or mixed methods and explored the main outcomes of peer mentoring programs. Eligible studies were appraised independently using the Joanna Briggs Institute (JBI) Critical Appraisal Checklists. Two independent reviewers extracted relevant data using a standardized form. A meta-analysis, narrative synthesis, and meta-aggregation were then conducted, followed by a convergent segregated approach to integrate the findings. Results: Thirty-one studies were selected for analysis. We aggregated four sets of synthesized findings from fourteen categories. A meta-analysis of the data showed that the intervention group experienced significant improvement in stress levels. In addition, the integrated results revealed peer mentors, with the support of academia, served as rich resources and support for peer mentees. Conclusion: This review highlights the importance of providing support to peer mentors to help them achieve the desired outcomes of peer mentoring while they cater to the needs of nursing student mentees. Highlights: Qualitative and quantitative data reveal benefits for peer mentors and mentees. Academia's involvement in peer mentoring is essential to achieving positive outcomes. The impacts of peer mentoring can be evaluated in academic and clinical settings.